Request Strategies in the TV Series Victorious - Windy Alviora Lestari; Thomas Joko Priyo Sembodo (Universitas Gadjah Mada, 2019)
This research aimed to investigate request strategies as found in an American TV series Victorious. In particular, it attempted to identify and classify request head acts, external modifications, and types of sentences of the requests expressed by the characters in the series. Therefore, utterances containing requests in the TV series were used as the data of this study. The results show that the most frequently used request strategy in the TV series was direct strategy (mood derivable) with 194 occurrences (67%). In addition, an external modification by means of grounder was found to be the most frequent strategy in the TV series with 32 occurrences (94% of the total number of the external modifications). Furthermore, it was found that the imperative sentence was the most frequent type of sentence utilized by the characters in the series when making requests with 216 occurrences (74%). In conclusion, the tendency for the characters to use mood derivable as their request strategy might due to their intimacy with each character and the informal situations and conversations where they interacted with each other throughout the TV series. In addition, the proclivity of the characters to use grounder may relate to ease and simplicity. Finally, the tendency of the characters to use declarative sentences when making requests might due to its simplicity and function to state facts, opinions, or ideas.